Pengembangan Masyarakat melalui Pemecahan Masalah Lingkungan oleh Pesantren di Mertapada Kulon - Asep Kurniawan (UIN Siber Syekh Nurjati Cirebon, 2023)
Solving environmental damage is no longer the sole authority of the government and related institutions, but the community and educational institutions are the main actors. This study presents how the efforts of the community and educational institutions to carry out various environmental care efforts. The data used was extracted from in-depth observations, in-depth interviews with communities and educational institutions in Mertapada Kulon and analyzed through data reduction, data display and data inference. The research findings showed that waste management in this village used the same waste bank management method. However, it had problems in Human Resources and lack of public awareness. Generally, recycling activities were limited to sorting waste and junk. Villages received financial support from the village. The solution to environmental problems was mostly pioneered by Nahdhatul Ulama figures. This research is wisdom to formulate a policy and strengthen the participation of the community and educational institutions for a sustainable environment